2007
DOI: 10.1038/sj.mp.4002089
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for induction of the ornithine transcarbamylase expression in Alzheimer's disease

Abstract: To more rapidly identify candidate genes located within chromosomal regions of interest defined by genome scan studies in Alzheimer's disease (AD), we have developed a customized microarray containing all the ORFs (n = 2741) located within nine of these regions. Levels of gene expression were assessed in total RNA from brain tissue of 12 controls and 12 AD patients. Of all genes showing differential expression, we focused on the ornithine transcarbamylase (OTC) gene on Xp21.1., a key enzyme of the urea cycle w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 42 publications
8
33
0
Order By: Relevance
“…In a complementary way, these different observations further confirm the well-documented presence of vascular dysfunctions in AD [54]. Interestingly, systematic transcriptomic approaches have shown that several genes are differentially expressed in the endothelium of brain capillaries in AD cases, relative to controls [55,56]. In particular, characterization of interleukin 33 as a potential genetic determinant of Ab40 secretion in vitro and cerebral amyloid angiopathy (CAA) in the AD brain could support a potentially relevant link between CAA formation, neurovascular dysfunction and alteration of immune cell functions [56].…”
Section: Strengthening Of the Amyloid Cascade Hypothesissupporting
confidence: 62%
“…In a complementary way, these different observations further confirm the well-documented presence of vascular dysfunctions in AD [54]. Interestingly, systematic transcriptomic approaches have shown that several genes are differentially expressed in the endothelium of brain capillaries in AD cases, relative to controls [55,56]. In particular, characterization of interleukin 33 as a potential genetic determinant of Ab40 secretion in vitro and cerebral amyloid angiopathy (CAA) in the AD brain could support a potentially relevant link between CAA formation, neurovascular dysfunction and alteration of immune cell functions [56].…”
Section: Strengthening Of the Amyloid Cascade Hypothesissupporting
confidence: 62%
“…Indeed, Bensemain et al showed evidence for: (i) an overexpression of OTC in brain vascular endothelial cells from patients with Alzheimer's disease; (ii) a significant association of the rs5963409 minor allele with an increased risk of disease onset; (iii) a putative functional significance of the rs5963409 minor allele as it was shown to abolish methylation of a CpG island within the promoter of the OTC gene. 20 Given the close association between hypertension and Alzheimer's disease, 30 these results are consistent with this study. Nevertheless, it will be necessary to experimentally validate the functional role of the rs5963409 minor allele and to assess the putative effect of the six other SNPs that are in complete LD with the rs5963409 polymorphism.…”
Section: Discussionsupporting
confidence: 89%
“…Of note, the rs5963409 polymorphism was of particular interest because the corresponding minor allele was shown to abolish the methylation of a CpG island within the promoter. 20 The rs1800321 polymorphism, not fully associated with the haplotype block (r 2 = 0.12), leads to a nonsynonymous substitution (Lys46Arg). Hence, the OTC SNPs selected for the association studies were the rs5963409 and the rs1800321 polymorphisms.…”
Section: Results Selection Of Relevant Snps For Association Studiesmentioning
confidence: 99%
“…On the other hand, OTC induction has been observed in vascular endothelial cells in brains of patients with Alzheimer´s disease. The OTC activity in the CSF of Alzheimer´s patients is several times higher than that in control subjects [5].…”
Section: Scopementioning
confidence: 99%